2012
DOI: 10.1002/jrs.4080
|View full text |Cite
|
Sign up to set email alerts
|

Micro Raman spectroscopy (MRS) and energy dispersive x‐ray microfluorescence (μEDXRF) analysis of pigments in the Iberian cemetery of Tutugi (from the fourth to the third century bc, Galera, Granada, Spain)

Abstract: Micro Raman spectroscopy (MRS) and energy dispersive x-ray microfluorescence (mEDXRF) analysis of pigments in the Iberian cemetery of Tutugi (from the fourth to the third century BC, Recent archaeological research on the Iberian cemetery of Tutugi (from fourth to third century BC), in the administrative term of Galera (Granada, Spain), has granted access to a range of materials revealing major features of Iberian culture. The only information available on pigments in the Iberian culture refers to domestic cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Sanchez et al . used MRS and energy dispersive X‐ray microfluorescence to analyze pigments in the Iberian cemetery of Tutugi, from the 4th to the 3rd century bc , Galera, Granada, Spain . Tomasini and co‐workers studied carbon‐based black pigments using MRS and found that Raman is an ideal technique for the characterization of carbonaceous matter .…”
Section: Art and Archeologymentioning
confidence: 99%
“…Sanchez et al . used MRS and energy dispersive X‐ray microfluorescence to analyze pigments in the Iberian cemetery of Tutugi, from the 4th to the 3rd century bc , Galera, Granada, Spain . Tomasini and co‐workers studied carbon‐based black pigments using MRS and found that Raman is an ideal technique for the characterization of carbonaceous matter .…”
Section: Art and Archeologymentioning
confidence: 99%
“…The contribution of Raman spectroscopy in 2012/2013 to the pigment identification and on conservation issues has been equally significant: pigments and plasters from the Roman settlement of Thamusida in Rabat, Morocco (Gliozzo et al); the tomb of Djehutyemhab (TT194), Elqurna necropolis, Upper Egypt (Mahmoud); pigments from five Medieval Gotland churches in Sweden (Nord and Tronner); the painted vaulted ceiling of the Sant Joan Del Mercat Church, Valencia, Spain (Doménech‐Carbó et al); 16th century wall paintings in the Saint Andrew Church, Biañez, Biscay, and Saint John the Baptist Church, Axpe, Biscay (Irazola et al); Sala delle Maschere of the Domus Aurea in Rome (Paradisi et al); pigments from the 4th to the 3rd century bc in the Iberian cemetery of Tutugi, Galera, Granada, Spain (Sánchez et al); Roman plasters applied over Pharaonic walls at Luxor temple, Upper Egypt (Mahmoud et al); chromatic alterations of Roman Heritage in Aosta (Conz et al) ; Roman mural paintings (Toschi et al); the fresco ‘The Good and the Bad Judge’ located at the medieval village of Monsaraz in southern Portugal (Gil et al); and multipigmented surface from the wall decorations of the Theban tomb (TT277), Luxor, Egypt (Mahmoud).…”
Section: Introductionmentioning
confidence: 99%
“…Technically, the use of cinnabar means decoration after firing, because cinnabar starts to change above 250 °C, it becomes black HgS between 335 and 386 °C and sublimates at 584 °C . Unlike other cases where cinnabar is applied on a layer of gypsum, red decoration in the vessel under study was applied directly on the ceramic surface.…”
Section: Resultsmentioning
confidence: 99%
“…This paper brings together previous analyses and accounts for the latest progress made by use of MRS in research on a variety of coverings and on decorated ceramics, especially on black decoration, whether alone or with grey and/or red decoration. Coverings and ceramics consist of the highest percentage of Iberian materials researched to this day.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation